Promoting vaccinations - an analysis of measures taken by German statutory health insurers - Kathrin Damm; Jana M. Schubert; J.-Matthias von der Schulenburg (Health Economics Review, 2011)
Introduction: Prophylactic vaccinations play a significant role in health care. As a relatively cost-effective preventive measure they can help to avert transmissible diseases and thus protect not only the vaccinated individuals themselves but also those who have not been vaccinated. In order to achieve this, a high vaccination rate is necessary; for many prophylactic vaccinations this rate is not reached in Germany. In order to counteract this trend the importance of prophylactic vaccinations was upgraded in 2007 within the scope of the reform of the health system. The reimbursement of patients' vaccination fees was made compulsory for the statutory health insurance companies and statutory requirements were imposed on the insurers to ensure a nationwide provision of prophylactic vaccinations for insured persons. The objective of this paper is to evaluate to what extent the health insurance companies promote the increasing of vaccination coverage rate today and what measures are being used to present this topic to the public. Methods: In order to assess the public presentation of the topic prophylactic vaccinations we have examined the websites of 68 statutory health insurance companies. We have assessed the attitude of the companies towards the promotion of participation in vaccination programs by conducting qualitative, structured interviews with representatives of 8 health insurers. Results: Measures to promote vaccinations, such as information, recall offers, projects to educate people or even monetary incentives, are employed relatively extensively by the health insurers and are considered important. However, it became clear that the discussion about prophylactic vaccinations, in particular concerning the costs and benefits thereof, had not been completed yet within the companies. Vaccination-specific data is not collected or evaluated on a regular or even isolated basis. There are no concrete targets concerning specific vaccination rates and incentives are neither evaluated nor compared with one another. Conclusions: The relatively extensive range of measures used to promote the vaccination rate contrasts with insufficient knowledge about their efficacy and efficiency. There is an urgent requirement for more research here.
Keywords: 330; vaccination; vaccination rate; health insurance; incentives; promotional measures